2020
DOI: 10.1088/1757-899x/721/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of printed circuit heat exchanger for supercritical carbon dioxide and water

Abstract: Printed circuit heat exchanger could be used as pre-cooler in the supercritical carbon dioxide (S-CO2) Brayton power cycle. Due to the drastic variations of S-CO2 properties in pre-cooler, segmental design method is used to investigate the thermal-hydraulic performance of PCHE. When the heat duty is given, the local heat transfer entropy generation number has extreme value, which appears near the intersection point of the heat capacity flow rates of both sides. In addition, the local and total entropy generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…On the refrigerant-side, the Gnielinski correlation [26] was used to calculate the Nusselt number: (13) which is valid in the range of 2300 < Re b < 10 6 .…”
Section: Refrigerant-side Heat Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…On the refrigerant-side, the Gnielinski correlation [26] was used to calculate the Nusselt number: (13) which is valid in the range of 2300 < Re b < 10 6 .…”
Section: Refrigerant-side Heat Transfermentioning
confidence: 99%
“…They described the variations of local heat transfer coefficient in the cooling process in the direction of the flow and proposed a more accurate heat transfer correlation. Zhang et al [13] evaluated the performance of a printed circuit heat exchanger for cooling CO 2 with water. The analysis concluded that rapid variations in the thermodynamic properties of supercritical CO 2 increase entropy generation and therefore, to optimize the second law efficiency of the investigated heat exchanger, higher CO 2 mass flow rates should be used.…”
Section: Introductionmentioning
confidence: 99%